Interlanguage pragmatics of requests situated in power and solidarity by Iraqi non-native and American native speakers of english in the academic setting - Turki, Hutheifa Yousif (2018)
Interlanguage pragmatics seeks to investigate how the non-native speakers’ strategies and patterns in expressing speech acts are different from or similar to those used by native speakers in academic setting. In this light, the current study contributes to the existing literature of interlanguage pragmatics by investigating the use of requests in academic setting by the Iraqi non-native speakers of English compared to that of American native speakers of English. The study comprises four objectives: 1. to compare the use of requests by the Iraqi non-native and American native speakers of English in academic setting, 2. to identify the Iraqi non-native and American native speakers of English’s use of requests in relation to power in the academic setting, 3. to identify the Iraqi non-native and American native speakers of English’s use of requests in relation to solidarity in the academic setting, and 4. to compare the Iraqi non-native and American native speakers of English’s sociopragmatic assessment of social factors in relation to the requests used in the academic setting. To address these objectives, a multimethod data collection approach was employed, namely (1) a written discourse completion task (WDCT), (2) a scaled-response questionnaire (SRQ), and (3) a retrospective interview to gather data related to the focus of the study. In total, 65 Iraqi non-native and 30 American native speakers of English identified via non-random convenience sampling, participated in the study. Two major theories were adopted in this study: Schuare’s (2009) taxonomy of request speech act, and Leech’s (2005) Grand strategy of politeness framework. Schuare’s taxonomy, which is based on Blum-Kulka et al.'s (1989) taxonomy of request speech acts was employed as a focal theory to statistically analyse quantitative data. Moreover, Leech's (2005) Grand Strategy of Politeness was utilized for the analysis of the respondents’ sociopragmatic assessment of the social variables in relation to requests. The data were also analysed quantitatively using Chi-square analyses and qualitatively, using thematic analysis to examine data obtained from the conducted interviews. The findings indicate that while the Iraqi non-native speakers of English tended to use more direct requests than the American native speakers of English, the latter used more conventionally indirect requests than the former in the academic setting. In addition, both the American native and Iraqi non-native speakers of English used frequently similar internal modifiers to make their requests sound more polite. Specifically, there were significant differences in the non-native and native speakers’ use of sub-strategies of internal modifiers. Similar use of external modifiers was evident in both groups’ data. Furthermore, the findings show that the use of polite requests by the Iraqi non-native and American native speakers of English was influenced by power and solidarity. Finally, the Iraqi non-native speakers of English seemed to show a developmental pattern different from the American native speakers in their assessment of the social variables, suggesting that their sociopragmatic knowledge is still under developed. Accordingly, Iraqi non-native speakers of English are required to improve their pragmalinguistic and sociopragmatic knowledge so as to express their requests appropriately, acceptable to the target language norms. The findings of this study would inform English language instructors on the teaching of appropriate requests and strategies that need to be used by non-native speakers, which in turn would enhance English learner’s pragmatic knowledge and the effectiveness of their communication with their interlocutors.